Mass media in post-1990 Nepal: Ajar window of mass communication - Duwadi, Eak Prasad (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5821 Bodhi 2010 4(1): 210-222